2022
DOI: 10.1038/s41467-022-28290-z
|View full text |Cite|
|
Sign up to set email alerts
|

Catastrophic slab loss in southwestern Pangea preserved in the mantle and igneous record

Abstract: The Choiyoi Magmatic Province represents a major episode of silicic magmatism in southwestern Pangea in the mid-Permian-Triassic, the origin of which remains intensely debated. Here, we integrate plate-kinematic reconstructions and the lower mantle slab record beneath southwestern Pangea that provide clues on late Paleozoic-Mesozoic subducting slab configurations. Also, we compile geochronological information and analyze geochemical data using tectono-magmatic discrimination diagrams. We demonstrate that this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 145 publications
0
17
0
Order By: Relevance
“…However, accurate correlations between Permian volcanic deposits, magmatic centres and emplacement mechanisms are lacking across large parts of the West Pangean/Gondwana proto-Pacific margin, particularly the Antarctic Peninsula. Castillo et al (2017) dated magmatism at ~255 Ma from Tierra del Fuego, which represents the southerly extent of Late Permian magmatism in South America (Gianni and Navarrete, 2022) and records a significant crustal component relative to magmatism further north. This episode of magmatism from Tierra del Fuego overlaps with the granitoid gneisses dated from eastern Graham Land and northwest Palmer Land (Millar et al, 2002;Riley et al, 2012;Castillo et al, 2020), andCastillo et al (2017) suggested a close link between southern Patagonia and the Antarctic Peninsula during the Late Permian (Fig.…”
Section: Permian (299-252 Ma)mentioning
confidence: 99%
See 4 more Smart Citations
“…However, accurate correlations between Permian volcanic deposits, magmatic centres and emplacement mechanisms are lacking across large parts of the West Pangean/Gondwana proto-Pacific margin, particularly the Antarctic Peninsula. Castillo et al (2017) dated magmatism at ~255 Ma from Tierra del Fuego, which represents the southerly extent of Late Permian magmatism in South America (Gianni and Navarrete, 2022) and records a significant crustal component relative to magmatism further north. This episode of magmatism from Tierra del Fuego overlaps with the granitoid gneisses dated from eastern Graham Land and northwest Palmer Land (Millar et al, 2002;Riley et al, 2012;Castillo et al, 2020), andCastillo et al (2017) suggested a close link between southern Patagonia and the Antarctic Peninsula during the Late Permian (Fig.…”
Section: Permian (299-252 Ma)mentioning
confidence: 99%
“…Primary volcanic successions crop out in central Patagonia (e.g. Gianni and Navarrete, 2022;Falco et al, 2022) and subvolcanic equivalents are preserved across large parts of Patagonia, into Tierra del Fuego and sectors of the Antarctic Peninsula (eastern Graham Land and western Palmer Land; Fig. 11).…”
Section: Permian (299-252 Ma)mentioning
confidence: 99%
See 3 more Smart Citations